2000
DOI: 10.1128/cdli.7.2.274-278.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Human T-Cell Lymphotropic Virus Type 1 Tax to Rabbits bytax-Only-Positive Human Cells

Abstract: The human T-cell lymphrotropic virus type 1 (HTLV-1) is causally related to adult T-cell leukemia and lymphoma and the neurodegenerative diseases tropical spastic paraparesis and HTLV-1-associated myelopathy. In the United States the prevalence of infection has been estimated to range from 0.016 to 0.1% on the basis of serologic tests for antibodies to the viral structural proteins. Blood from donors positive for antibodies to HTLV-1 or HTLV-2 is not used for transfusion. However, patients with the cutaneous T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…MF patients are HTLV-1 seronegative; however, several groups revealed HTLV-1 markers in MF patients, namely tax -like sequences (second exon 159-bp-long fragment) [24,[25][26][27][28][47][48][49] and HTLV-1 dgs [29,30] . In addition, HTLV-1-positive cell lines were established from PBMCs of MF patients that were HTLV-1 seropositive [50] , seronegative or seroindeterminate [51,52] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MF patients are HTLV-1 seronegative; however, several groups revealed HTLV-1 markers in MF patients, namely tax -like sequences (second exon 159-bp-long fragment) [24,[25][26][27][28][47][48][49] and HTLV-1 dgs [29,30] . In addition, HTLV-1-positive cell lines were established from PBMCs of MF patients that were HTLV-1 seropositive [50] , seronegative or seroindeterminate [51,52] .…”
Section: Discussionmentioning
confidence: 99%
“…Some of the results suggest that tax transmission occurs with mononuclear cells [27] , where tax may be present as an extra chromosomal sequence [33] .…”
mentioning
confidence: 98%
“…The risk of transmitting human retroviruses (HRV), such as human immunodeficiency virus (HIV) and human T-lymphotropic viruses types I and II (HTLV-I/II), has been reduced drastically due to screening for the corresponding antibodies. However, recently there have been reports of HTLV-I seronegative blood donors who harbor the tax sequence [40,42,43,44]. p40 tax protein, encoded by HTLV-I tax, is not only the transactivator of the long terminal repeat of the virus, but is also implicated in transcriptional regulation of numerous cellular growth factors, cytokines, and oncogenes [4,8,11,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Zucker-Franklin showed that seronegative Taxonly positive MF patients as well as healthy Tax-only positive blood donors can transmit Tax to rabbits. However, in our study with MF patients, the rats inoculated with the MF patients PBMC developed antibodies not only to the Tax antigens as in the study of Zucker-Franklin [32] but also to p21, gp46 envelope and p24 gag antigens.…”
Section: Discussionmentioning
confidence: 74%